2019
DOI: 10.1186/s13104-019-4702-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with food safety practices among food handlers: facility-based cross-sectional study

Abstract: ObjectiveThe primary objective of this study was to assess factors associated with food safety practices among food handlers in Gondar city food and drinking establishments. The facility-based cross-sectional study was undertaken from March 3 to May 28, 2018, in Gondar city. Simple random sampling method was used to select both establishments and the food handlers. The data were collected through face-to-face interview using pre-tested Amharic version of the questionnaire. Data were entered and coded into Epi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
56
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 25 publications
(38 reference statements)
26
56
10
1
Order By: Relevance
“…Studies have revealed that, the probability of having good food safety practice was higher among food handlers supervised by health professionals [16,21]. However, fi ndings of this study…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Studies have revealed that, the probability of having good food safety practice was higher among food handlers supervised by health professionals [16,21]. However, fi ndings of this study…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore, to reduce foodborne illnesses, it is crucial to explore the sanitary and hygienic conditions of food providing services [15]. Ensuring safe food service has been one of the major challenges and concerns for producers, consumers and public health offi cials [16]. In Eritrea, even though there is no published data available about food safety, it is assumed that every year many people suffer and even die to the intake of contaminated food and water.…”
Section: Introductionmentioning
confidence: 99%
“…An outbreak of foodborne disease outbreaks in hospitals can lead to service disruption, life threatening diseases and even death for anyone who is infected, especially the already vulnerable patients [14]. Inadequate food handling practice among food handlers have been found to be associated with low levels of food safety knowledge [15]. The food service facilities in hospitals in the Capricorn District Municipality procure raw food materials and prepare meals for hospitalised people.…”
Section: Introductionmentioning
confidence: 99%
“…An outbreak of foodborne disease outbreaks in hospitals can lead to service disruption, life threatening diseases and even death for anyone who is infected, especially the already vulnerable patients [15]. Inadequate food handling practice among food handlers have been found to be associated with low levels of food safety knowledge (16). The food service facilities in hospitals in the Capricorn District Municipality procure raw food materials and prepare meals for hospitalised people.…”
Section: Introductionmentioning
confidence: 99%